Acoustical characterization of bone using a cylindrical model and time of flight method: edge reconstruction and ultrasound velocity determination in cortical bone and in medullar marrow - Detti, Valérie; Kourtiche, Djilali; Nadi, M (Physiological measurement, 2002)
Our objective is to evaluate the external and internal dimensions of bone diaphysis and the speed of sound in cortical bone and in medullar marrow. The diaphysis is modelled by a cylindrical hollow tube. The theory of rays is used and an approximation allows us to break free from the data gained by ultrasonic field amplitude. Then, acoustical and dimensional parameters are only related to the time of flight of reflected and transmitted acoustic echoes in the tube. From the arrival time of particular echoes, the inverse problem resolution then allows us to experimentally determine the sought parameters. This method is validated in vitro on a bovine femur and gives satisfactory results.